New control method for the industrial process of cookies manufacturing - Ureña-Peralta, Milber Oswaldo; Luyo-Cordova, Jimena Danixa; Chire-Fajardo, Gabriela Cristina (Revista Colombiana de Investigaciones Agroindustriales, 2020)
The Biostructured Process Control Method (BCPM) is a new method similar to the Balance Score Card dashboard with a quantitative control based on compliance with standards which was applied in the industrial manufacture of cookies. The control biostructure, designed considering the characteristics of the process, was made up of five sub-processes (mixing, molding, baking, sandwiching and packaging) and three sub-processes as part of the mixing sub-process; also, 16 control parameters were identified. Control variable data were evaluated over a five-month period. The control was performed according to the efficacies of the sub-processes and control variables, for which target values were set. During the evaluation period, the process achieved between 95% and 98.1% of efficacy, as the company required 95% to meet internal standard. Opportunities for improvement were identified in sub-processes with lower efficacies. This method can be applied in the food industry to identify deficiencies in production processes.